1992
DOI: 10.1007/bf00927118
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and psychopathology among adolescents with severe emotional disturbances

Abstract: Family psychosocial functioning and its relation to psychopathology among adolescents with severe emotional disturbances (SED) was assessed. Subjects were 353 adolescents with SED, ages 12-18, and their parents. During a semi-structured interview, adolescents were administered Family Adaptability and Cohesion Evaluation Scale (FACES-III), Diagnostic Interview Schedule for Children-Child Version (DISC-C), and the Self-Derogation Scale. Parents were administered FACES-IIII and the Child Behavior Checklist (CBCL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 16 publications
4
36
1
5
Order By: Relevance
“…The published version is available at http://www.apa.org/journals/abn/ NIH Public Access The most widely-reported finding with regard to family processes is that depression is inversely related to the level of support, attachment, and approval adolescents experience in the family environment. This result has been replicated in both community (e.g., Avison & McAlpine, 1992;Garrison, Jackson, Marsteller, McKeown, & Addy, 1990;McFarlane, et al, 1994;Scaramella, Conger, & Simons, 1999) and clinical samples (e.g., Pavlidis & McCauley, 2001;Prange, Greenbaum, Silver, Friedman, Kutash, & Duchnowski, 1992;Sheeber & Sorensen, 1998). Depression has also been found to be associated with parent and adolescent reports of conflictual family interactions (Stark, Humphrey, Crook, & Lewis, 1990;Cole & McPherson, 1993;Sheeber & Sorensen, 1998).…”
Section: Publisher's Disclaimermentioning
confidence: 75%
“…The published version is available at http://www.apa.org/journals/abn/ NIH Public Access The most widely-reported finding with regard to family processes is that depression is inversely related to the level of support, attachment, and approval adolescents experience in the family environment. This result has been replicated in both community (e.g., Avison & McAlpine, 1992;Garrison, Jackson, Marsteller, McKeown, & Addy, 1990;McFarlane, et al, 1994;Scaramella, Conger, & Simons, 1999) and clinical samples (e.g., Pavlidis & McCauley, 2001;Prange, Greenbaum, Silver, Friedman, Kutash, & Duchnowski, 1992;Sheeber & Sorensen, 1998). Depression has also been found to be associated with parent and adolescent reports of conflictual family interactions (Stark, Humphrey, Crook, & Lewis, 1990;Cole & McPherson, 1993;Sheeber & Sorensen, 1998).…”
Section: Publisher's Disclaimermentioning
confidence: 75%
“…Similar fi ndings occur in non-abusive samples. An investigation of adolescents and their parents showed that low cohesion scores were associated with conduct-disordered behaviors, depression, and substance abuse (Prange et al, 1992). Family adaptability scores were correlated with conduct-disordered behaviors and anxiety (Prange et al, 1992).…”
Section: The Parent-child Relationship and Parenting Beliefsmentioning
confidence: 99%
“…De plus, la dépression est 33 inversement reliée au soutien, à l'attachement et à l'approbation apportés par la famille (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990;Avison & McAlpine, 1992;Barrera & Garrison-Jones, 1992;Hops, Lewinsohn, Andrews, & Roberts, 1990;Kandel & Davies, 1982;McFarlane, Bellissimo, Norman & Lange, 1994;Prange, Greenbaum, Silver, Friedman, Kutash & Duchnowski, 1992). Des adolescents déprimés rapportent que leurs parents sont moins chaleureux (Heights, Field, Diego & Sanders, 2001;Rey, 1995) et leur fournissent moins de soutien comparativement aux adolescents non déprimés (Hoffman & Su, 1998 (Garber, Robinson, Valentiner, 1997;Rey, 1995).…”
Section: 'Appartenance /Implication Dans La Relation Et La Dépressiunclassified
“…En effet, plusieurs chercheurs ayant mesuré des variables semblables à 79 l'appartenance / implication dans la relation en lien avec la dépression observent une relation négative entre ces deux variables. Ainsi, une corrélation négative est remarquée entre le soutien, l'attachement et l'approbation en provenance de la famille et la dépression chez des adolescents (Armsden, McCauley, Greenberg, Burke, & Mitchell, 1990;Avison & McAlpine, 1992;Barrera & Garrison-Jones, 1992;Hops, Lewinsohn, Andrews, & Roberts, 1990;Kandel & Davies, 1982;McFarlane, Bellissimo, Norman & Lange, 1994;Prange, Greenbaum, Silver, Friedman, Kutash & Duchnowski, 1992). Les adolescents qui reçoivent du soutien des deux parents présentent moins de symptômes dépressifs que ceux vivant avec un ou deux parents non soutenants (Patten, Gillin, Farkas, Gilpin, Berry, & Pierce, 1997).…”
Section: Relation Entre Comportements Interpersonnels Et Dépressionunclassified